The role of scouting and guiding camps in the development of social capital of Omani youth - Bamsilah, Donia Selim Massoud (Journal of Humanities & Social Sciences, 2022)
The study aimed to investigate the role of scouting and guiding camps in the development of social money amng young people in October 2019. The study relied on the descriptive analytical approach, where a tool was used to collect data, and it was directed to scouts and risks. The interest of the results of the study in the development of the social and extension camp has a role in the development of the young social community, and that is through the activities that it practices in the camp and its interaction with its colleagues and with leaders and leaders, In addition to the previous results, the study revealed a number of difficulties that limit the role of scouting and guiding camps in the development of social capital, including administrative, material, cultural and social difficulties and difficulties associated with scouts and guides themselves. The study ended with reaching some general conclusions based on the results of the study, as well as developing proposals that might help in overcoming the difficulties that limit the role of scouting and guiding camps in developing the social capital of Omani youth.
Keywords: camp; scouts; guides; planning; life